Could fertility-sparing surgery be considered for stage I ovarian sex cord-stromal tumors? A comparison of the Fine-Gray model with Cox model - Sun, Dan; Zhi, Zhi F.; Fan, Jiang T. (Frontiers in Oncology, 2022)
Objective To evaluate the oncologic outcomes in patients with International Federation of Gynecology and Obstetrics (FIGO) stage I ovarian sex cord-stromal tumors (SCSTs) who underwent fertility-sparing surgery (FSS) and the independent risk factors affecting overall survival (OS) and cancer-specific survival (CSS). Methods Data were acquired from the Surveillance, Epidemiology, and End Results (SEER) database between 1973 and 2018. A total of 240 patients diagnosed with stage I ovarian SCSTs were divided into the definitive surgery group (N=116) and FSS group (N=124). The Kaplan-Meier analysis and Cox model were used to evaluate the overall survival (OS) and cancer-specific survival (CSS) of the two groups and assess the independent risk factors respectively. The Fine-Gray model evaluated cancer-specific mortality (CSM) and the independent risk factors that affected CSM. Results Kaplan-Meier survival analysis showed no statistically significant differences in OS and CSS between the two groups (P>0.05). Univariate analysis of the Fine-Gray model also showed that there was no difference in the CSS between the two groups (P>0.05). However, from the 15th year postoperatively, the CSS of the FSS group decreased by 13.21% compared with that of the control group and by 17.49% in the 20th and 25th years postoperatively. The Cox proportional hazards model found that surgical methods (“defined surgery” vs “FSS”; HR=0.03259, P=0.0196) and FIGO stage (“stage IA” vs “stage IC” ; HR=0.03073, P=0.0300) were independent risk factors for OS. The multivariate analysis of Fine-Gray model showed that the cancer-specific mortality of patients receiving definitive surgery was 40.1% lower than that of patients receiving FSS (“definitive surgery” vs “FSS”; HR=0.599, P=0.005), indicating that FSS might lead to higher tumor-specific mortality and lower CSS. However, age, race, laterality, history, FIGO stage, and tumor size had no significant influence on the tumor-specific mortality (P>0.05). Conclusions FSS is considered for patients with stage I SCSTs with reproductive needs, but the follow-up period should not be less than 15 years. For patients with stage IC disease, FSS should be selected carefully, and close follow-up is necessary. Perhaps, definitive surgery after birth is a means to improve long-term survival rates.